A qualitative analysis of human-agent functions for collaborative multi-agent system - Mohammed K.A.; Mostafa S.A.; Ahmad M.S.; Mahmoud M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Autonomous agents; Computational methods; Intelligent agents; Multi agent systems; Surveys; Agent-based model; collaboration; Collaborative multi-agent systems; Generalized functions; Human agent; Qualitative analysis; Questionnaire surveys; Workflow process; Software agents